2004
DOI: 10.1002/nvsm.259
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the postgraduate education market for UK‐based students: a review and empirical study

Abstract: This paper examines why postgraduate students in the UK decide to take up a further degree, the factors influencing their choice of programme and institution and the sources of information consulted. The study is based on a literature review, other sources of information and primary research with students at one institution. Based on responses from 102 current students the analysis reveals that improvement of career prospects was the prime motivator for studying a postgraduate qualification, allied to a desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 10 publications
4
40
0
4
Order By: Relevance
“…relying on the product to sell, towards a more "customer-led" approach (Angell, Heffernan, & Megicks, 2008). It has been found that when making the uncertain and high-risk decision of choosing a university, the student looks for evidence of service quality (Donaldson & McNicholas, 2004). This confirms the importance of service quality in the university's functions.…”
Section: Introductionmentioning
confidence: 84%
“…relying on the product to sell, towards a more "customer-led" approach (Angell, Heffernan, & Megicks, 2008). It has been found that when making the uncertain and high-risk decision of choosing a university, the student looks for evidence of service quality (Donaldson & McNicholas, 2004). This confirms the importance of service quality in the university's functions.…”
Section: Introductionmentioning
confidence: 84%
“…Education quality, reputation, and location are the key factors influencing a decision to study abroad (Kend et al, 2017). Universities that retain postgraduate students contribute to the country economic welfare, boost lifelong learning and exploit innovative areas of research (Donaldson & McNicholas, 2004). It is the key success for universities to keep up with the state of art relationship marketing strategies to survive in the highly competitive environment (Curth et al, 2019;Helgesen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For many students, personal satisfaction and new skill acquisition is an important consideration in their decision to undertake further study (Pratt, Hillier, & Mace, 1999). For others, postgraduate study is related to a career change (Donaldson & McNicholas, 2004). In Australia, a change in the certification process by the Safety Institute of Australia (SIA) now requires members to have a minimum relevant education level in Occupational Health and Safety (OHS).…”
Section: Discussionmentioning
confidence: 99%